The Impact of Assets Disposal and Economic Crisis on the Valuation of Asset Write-offs - Mohd-Saleh, Norman; Jaffar, Romlah (Journal of Business Management and Accounting, 2011)
The financial crisis that occurred in Malaysia in the last decade followed by a series of corporate restructuring exercises trigger some fi rms to write off assets value. The incentives to write off may come from signalling future distress, current restructuring exercises, or taking the opportunity to blame the crisis. This scenario creates an opportunity to investigate the market reaction on different causes of asset write-off during a crisis period which is not found in prior studies. This paper examines the effect of specifi c events such as asset disposal and economic crisis on the valuation of asset write-offs. Asset write-offs related to disposal of assets (likely to be associated with streamlining business activities) and economic crisis (a factor beyond the control of the fi rm) are expected to receive less negative impact from the market compared to write-off events not associated with a disposal or crisis. The data consists of listed non-fi nancial fi rms on Bursa Malaysia (3,301 fi rm-years) from fi nancial year 1990 to 2000. A multivariate regression model is used to test the prediction. We fi nd results which are not consistent with the predictions. One possible reason that can explain the results is that the market interprets asset write-offs to be associated with big-bath activities which subsequently would result in more discounts attached to such write-off.